Nilai Nutrisi Umbi Ubijalar [Ipomoea batatas (L.) Lamb.] yang Dikonsumsi Bayi dan Anak-anak Suku Dani di Distrik Kurulu Kabupaten Jayawijaya - Andrew B. Pattikawa; Antonius Suparno; Saraswati Prabawardani (Program Pascasarjana Universitas Papua, 2018)
Sweet potato is an important staple food crop especially for the local people of Central Highlands Jayawijaya. There are many accessions that have always been maintained their existence to enrich the types of consumption. Traditionally, sweet potato accessions were grouped based on the utilization, such as for animal feed, cultural ceremonies, consumption for adults, as well as for for children and infants. This study was aimed to analyze the nutritional value of sweet potatoes consumed by infants and children of the Dani tribe. Chemical analyses were conducted at the Laboratory of Post-Harvest Research and Development Center, Cimanggu, Bogor. The results showed that each of 4 (four) sweet potato accessions, which were consumed by infants and children, had diverse nutrient levels. Accession Sabe showed the highest water content (72.56%), vitamin C (72.71 mg/100 g), Fe (11.85 mg/100 g), and K levels (130.41 mg / 100 grams). The highest protein content (1.44%), fat (1.00%), energy (154.43 kkal/100 gram), carbohydrate (35.47%), starch (30.26%), reducing sugar (3.44%), riboflavin (0.18 mg/100 g), and vitamin A (574.40 grams IU/100) were produced by accession Manis. On the hand, accession Saborok produced the highest content of ash (1.32%), vitamin E (28.30 mg/100 g), and B-carotene (64.69 ppm). The highest level of crude fiber (1.81 %) and thiamin (0.36 mg/100 g) were produced by accession Yuaiken.